The adoption of e-commerce for wood enterprises. (8th April 2009) - Andreopoulou, Z.S.; Koutroumanidis, T.; Manos, B.
Lately, the internet has become a major means in electronic commerce (e-commerce), as it offers various advantages and benefits. In Greece, there are many Small- and Medium-sized Enterprises (SMEs) in the context of the timber trade and the wood processing and products sector that have already created a web presence in various stages of maturity. This paper studies the adoption of e-commerce in websites that support e-commerce activities within the timber trade and the wood processing and products sector. Therefore, the paper aims to identify and evaluate their qualitative and quantitative content characteristics, classify them as to their geographical distribution, rank them according to 13 content characteristics/criteria using the multicriteria method of PROMETHEE II and classify them in groups of similar adoption. The case of Greece was selected and the retrieved websites were studied and then ranked and classified accordingly. The findings of this study reveal the rate of adoption of e-commerce in the sector and can be a valuable model for the designers of the websites that promote e-commerce activities within the wider area of wood.